Perubahan Stratifikasi Sosial Masyarakat Bugis di Kabupaten Bone (Dalam Perspektif Pendidikan) - Widya Karmilasari (Paedagogik, 2013)
Social stratification is a class or order system in a comnvunity. Buginese people have been long familiar with the so called